Alberto Flores Galindo y Armando Nieto Vélez S.J. - Flores Galindo, Alberto (Pontificia Universidad Católica del Perú, Archivo de la Universidad, 1988)
Alberto Flores Galindo y el Padre Armando Nieto Vélez S.J.
1 fotografía : byn
Keywords: Flores Galindo, Alberto, 1949-1990; Nieto Vélez, Armando, S.J.; https://purl.org/pe-repo/ocde/ford#6.00.00